Are you there God? it's me, Margaret [videorecording (DVD)] - Fremon, Kelly; McAdams, Rachel, 1978-; Fortson, Abby Ryder, 2008-; Graham, Elle; Safdie, Benny; Kellum, Echo, 1982-; Bates, Kathy, 1948-; Zimmer, Hans; Blume, Judy (Lionsgate, 2023)
For over fifty years, Judy Blume's classic has connected with readers through its relatable story, achingly funny details, and candid exploration of life's biggest questions. In Lionsgate's big-screen adaptation, eleven-year-old Margaret is uprooted from her life in New York City for the suburbs of New Jersey, going through the messy and tumultuous throes of puberty with new friends in a new school. She relies on her mother, Barbara, who is also struggling to adjust to life outside the big city, and her adoring grandmother, Sylvia, who isn't happy they moved away and likes to remind them every chance she gets.